2016
DOI: 10.1001/jamaophthalmol.2016.0913
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Tumor Diameter in Association With Gene Expression Profile for Uveal Melanoma

Abstract: IMPORTANCE Uveal melanoma (UM) can be divided into prognostically significant subgroups based on a prospectively validated and widely used 15-gene expression profile (GEP) test. Class 1 UMs have a low risk and class 2 UMs have a high risk for metastasis.OBJECTIVE To determine whether any clinicopathologic factors provide independent prognostic information that may enhance the accuracy of the GEP classification. DESIGN, SETTING, AND PARTICIPANTSThis retrospective observational study performed at 2 ocular oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
3
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 18 publications
9
83
3
3
Order By: Relevance
“…RNA and its inherent instability compared to DNA may be more prone to handling error, and perhaps this may be the source of an inherently inaccurate test in the setting of GEP. It has also been suggested that the size of the tumor must be considered when interpreting a Class 1 or a Class 2 test result [21]. However, we found that the average tumor size was not statistically different between concordant and discordant groups of patients in our series.…”
Section: Discussioncontrasting
confidence: 74%
“…RNA and its inherent instability compared to DNA may be more prone to handling error, and perhaps this may be the source of an inherently inaccurate test in the setting of GEP. It has also been suggested that the size of the tumor must be considered when interpreting a Class 1 or a Class 2 test result [21]. However, we found that the average tumor size was not statistically different between concordant and discordant groups of patients in our series.…”
Section: Discussioncontrasting
confidence: 74%
“…26,27 Other authors have since also addressed the question as to whether the combined use of the TNM/AJCC staging system and genomic characteristics of the tumor will allow for better risk stratification. 28,29 As proposed earlier, 8,26,27 integrating the TNM/AJCC staging system with genetics may enhance prognostication in UM. This is supported by the findings of a recent study by Bagger et al 30 in a Danish cohort of 153 patients, which indicated that AJCC stage III and aberrations in chromosome 3 and 8 are independent prognostic factors.…”
mentioning
confidence: 95%
“…As a greater proportion of smaller tumors are being treated, recent research has demonstrated that in addition to a class 2 gene expression profile, LBD is also an independent statistically significant predictor of survival [18,19]. This suggests that metastasis is not only a product of a tumor's RNA activity, but also a result of tumor size [18,19,27].…”
Section: Discussionmentioning
confidence: 99%